Radiation of long and high power arcs. (17th September 2015) - Cressault, Y; Bauchire, J M; Hong, D; Rabat, H; Riquel, G; Sanchez, F; Gleizes, A
Abstract: The operators working on electrical installations of low, medium and high voltages can be accidentally exposed to short-circuit arcs ranging from a few kA to several tens of kA. To protect them from radiation, according to the exposure limits, we need to characterize the radiation emitted by the powerful arc. Therefore, we have developed a general experimental and numerical study in order to estimate the spectral irradiance received at a given distance from the arc. The experimental part was based on a very long arc (up to 2 m) with high ac current (between 4 and 40 kA rms, duration 100 ms) using 3 kinds of metallic contacts (copper, steel and aluminium). We measured the irradiance received 10m from the axis of the arc, and integrated on 4 spectral intervals corresponding to the UV, visible, IRA  +  B and IRC. The theoretical part consisted of calculating the radiance of isothermal plasmas in mixtures of air and metal vapour, integrated over the same spectral intervals as defined in the experiments. The comparison between the theoretical and experimental results has allowed the defining of three isothermal radiation sources whose combination leads to a spectral irradiation equivalent to the experimental one. Then the calculation allowed the deduction of the spectral description of the irradiance over all the wavelength range, between 200 nm and 20 μ m. The final results indicate that the influence of metal is important in the visible and UVA ranges whereas the IR radiation is due to the air plasma and surrounding hot gas and fumes.